Magnetic resonance neurography: normal values and demographic determinants of nerve caliber and T2 relaxometry in 60 healthy individuals - Kronlage, Moritz; Münch, Véronique; Schwarz, Daniel; Godel, Tim; Heiland, Sabine; Bendszus, Martin; Bäumer, Philipp (Clinical neuroradiology, 2019)
Purpose: To establish normal values and to identify demographic determinants of quantitative biomarkers in magnetic resonance neurography (MRN).MethodsIn this study 60 healthy individuals (5 men and 5 women of every decade between 20 and 80 years) were examined according to a standardized MRN protocol at 3 T, including multiecho T2 relaxometry. Nerve cross-sectional area (CSA), transverse relaxation time (T2), and proton spin density (PSD) were assessed for the sciatic, tibial, median, ulnar, and radial nerves. Correlation with demographic variables, such as height, weight, body mass index (BMI), and age was expressed by Pearson coefficients and t‑tests were used to compare MRN biomarkers between men and women with and without normalization to body weight and BMI by linear regression. Results: The average nerve CSA correlated moderately with height (r = 0.28, p = 0.04), weight (r = 0.40, p = 0.002), and BMI (r = 0.35, p = 0.008), but not with age (r = 0.23, p = 0.09). While T2 did not correlate with demographic parameters, PSD was strongly inversely associated with BMI (r = −0.64, p < 0.001) and weight (r = −0.557, p < 0.001). Sex-dependent differences in imaging marker values were found for CSA but became negligible after normalization to body weight. Conclusion: Quantitative biomarkers of MRN co-vary with demographic variables. As particularly important determinants, we identified body weight for nerve CSA and BMI for PSD. The presented normal values and demographic determinants may assist investigations into the potential of MRN biomarkers in further disease-specific studies.
First online: 13 October 2017
Gesehen am 04.04.2019